Inside Academia : Professors, Politics, and Policies - Cahn, Steven M. (Rutgers University Press, 2018)
Drawing on decades of experience as a renowned teacher, advisor, administrator, and philosopher, Steven M. Cahn diagnoses problems plaguing America's universities and offers his prescriptions for improvement. He explores numerous aspects of academic life, including the education of graduate students, the quality of teaching, the design of liberal arts curricula, and the procedures for appointing faculty and considering them for tenure. Inside Academia uses real cases to illustrate how faculty members, deans, and provosts often do not serve the best interests of schools or students. Yet the book also highlights efforts of those who have committed themselves and their institutions to the pursuit of academic excellence.